2022
DOI: 10.1002/tea.21756
|View full text |Cite
|
Sign up to set email alerts
|

The effectiveness of an integratedSTEMcurriculum unit on middle school students' life science learning

Abstract: Recent calls for reform in K-12 science education and the National Academy of Engineering's Grand Challenges for Engineering in the 21st Century emphasize improving science teaching, students' engagement, and learning. In this study, we designed and implemented a curriculum unit for sixth-grade students (i = 1305). The curriculum unit integrated science and engineering content and practices to teach ecology, water pollution, and engineering design. We investigated the designed integrated STEM unit's effectiven… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(4 citation statements)
references
References 76 publications
1
3
0
Order By: Relevance
“…Accordingly, these results indicated that the STEM-based learning environment is more effective than the curriculum-based learning environment in improving student achievement. This result is compatible with literature showing that STEM learning environments positively effect academic achievement and science learning (Akkaya, 2019;Angwal et al, 2019;Anwar et al, 2022;Büyükbastırmacı, 2019;Cotabish et al, 2013;Çalışıcı, 2018;Çetin, 2019;Dedetürk et al, 2020;Doğan, 2019;Fan & Yu, 2017;Gazibeyoğlu, 2018;Green, 2012;Gülen, 2016;Kapan, 2019;Koca, 2018;Yıldırım, 2016). Angwal et al (2019) reported that the STEM learning environment, which includes the engineering design process, is more effective than the traditional learning environment in improving students' science achievement.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…Accordingly, these results indicated that the STEM-based learning environment is more effective than the curriculum-based learning environment in improving student achievement. This result is compatible with literature showing that STEM learning environments positively effect academic achievement and science learning (Akkaya, 2019;Angwal et al, 2019;Anwar et al, 2022;Büyükbastırmacı, 2019;Cotabish et al, 2013;Çalışıcı, 2018;Çetin, 2019;Dedetürk et al, 2020;Doğan, 2019;Fan & Yu, 2017;Gazibeyoğlu, 2018;Green, 2012;Gülen, 2016;Kapan, 2019;Koca, 2018;Yıldırım, 2016). Angwal et al (2019) reported that the STEM learning environment, which includes the engineering design process, is more effective than the traditional learning environment in improving students' science achievement.…”
Section: Discussionsupporting
confidence: 92%
“…Therefore, researchers worldwide are conducting various research on STEM education. For example, studies have investigated the effects of STEM education on variables such as achievement, science content knowledge, motivation, attitude, problem-solving, higher-order thinking skills, and career interest (e.g., Angwal et al, 2019;Anwar et al, 2022;Cotabish et al, 2013;Fan & Yu, 2017;John et al, 2016;Kopcha et al, 2017;Lam et al, 2008;Lin et al, 2019;Ngo, 2021;Nugent et al, 2015). As stated earlier, STEM has become a focus area for education in Türkiye in recent years.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Johnson and the researchers have a long‐established partnership as teacher‐researchers. In the past, Mrs. Johnson had previously worked with Guzey in a professional development program on developing life science and engineering design curricula (Anwar et al, 2022). For two consecutive summers, Mrs. Johnson and two other participating teachers and research personnel spent three weeks developing an integrated science and engineering curriculum that explicitly integrated engineering design into a life science curriculum.…”
Section: Methodology and Methodsmentioning
confidence: 99%